Sofosbuvir with peginterferon‐ribavirin for 12 weeks in previously treated patients with hepatitis C genotype 2 or 3 and cirrhosis. Issue 3 (30th January 2015) - Lawitz, Eric; Poordad, Fred; Brainard, Diana M.; Hyland, Robert H.; An, Di; Dvory‐Sobol, Hadas; Symonds, William T.; McHutchison, John G.; Membreno, Fernando E.
Abstract : Sofosbuvir (SOF) in combination with ribavirin (RBV) for 12 or 24 weeks is the current standard of care for patients infected with hepatitis C virus (HCV) genotypes 2 and 3, respectively. However, in clinical trials treatment‐experienced patients, particularly those with cirrhosis, had suboptimal sustained virological response (SVR) rates. We assessed the efficacy and safety of sofosbuvir plus peginterferon and ribavirin (SOF+Peg‐IFN+RBV) administered for 12 weeks to treatment‐experienced patients with HCV genotypes 2 and 3, with and without cirrhosis. We enrolled 47 patients in this open‐label, nonrandomized, uncontrolled phase 2 study. The primary endpoint was the proportion of patients with SVR at 12 weeks after cessation of study treatment (SVR12). The overall rate of SVR12 was 89% (95% confidence interval [CI]: 77‐97). Rates of SVR12 were higher in patients with genotype 2 than in those with genotype 3, 96% (95% CI: 78‐100) and 83% (95% CI: 62‐95), respectively. Rates of SVR12 were similar in patients with and without cirrhosis: for genotype 2, 93% of patients with cirrhosis and 100% of patients without cirrhosis achieved SVR12, and for genotype 3, the SVR12 rate was 83% in patients both with and without cirrhosis. One patient discontinued study treatment because of an adverse event and four patients experienced serious adverse events. The most common adverse events were influenza‐like illness, fatigue, anemia, and neutropenia. Conclusion : In treatment‐experienced patients with HCV genotypes 2 and 3, 12‐week administration of SOF+Peg‐IFN+RBV provided high SVR rates, irrespective of cirrhosis status. No safety concerns were identified. (Hepatology 2015;61:769–775)